“‘Once more unto the Breach’: Professional Responsibility and Computer Ethics”. - Gotterbarn, Don (Science & Engineering Ethics, 2008)
The author discusses a paper by James Stieb which criticizes his work on professional responsibility in computing. He claims that he finds it hard to comment on Stieb's paper because many of the positions attacked by Stieb were not from him. The author points out the weakness of the move of Stieb to use guilt by association to prove that he supports a checklist approach to computer ethics. He adds that Stieb is being unreasonable for claiming that the book "Computer Ethics and Professional Responsibility" advocates the checklist approach.